LANGUAGE DISORDERS: STUTTERING ANALYSIS OF A 13-YEAR-OLD BOY (A PSYCHOLINGUISTIC STUDY) - Nabila Maulydia Chairun Nisa HP (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2024)
Psycholinguistics pertains to the cognitive condition of a person, which is influenced by their capacity to generate language. However, stuttering is a type of language disorder. Stuttering is when speech lacks structure, interrupts abruptly, and causes confusion for the listener. Therefore, this study aims to determine a total of language forms of fluency disorder experienced by a 13-year-old boy through five types of characteristics of stuttering. There are extending the sounds, repetition, pause, interjection, and ambiguity. The methodology used in this study is a qualitative-descriptive design using document research as collective data. This study found 7 data on stuttering experienced by the speaker, with one data extending the sounds, four data repetitions consisting of repetition of syllables, and two data from pauses. From this study, when there is a stutter when speaking, the speaker can control it with no excessive anxiety when there are pauses in his speech. The speaker looks calmer in dealing with situations when his stuttering occurs. From this study, when there is a stutter when speaking, the speaker can control it with no excessive anxiety when there are pauses in his speech. The speaker looks calmer in dealing with situations when his stuttering occurs. This situation can happen if someone experiencing stuttering desires to recover by doing treatment so that the language produced when speaking becomes softer, more fluent, and louder when spoken.